Role of HRM Practices in Performance of Organization and Employee Retention (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Human resource management methods are examined in relation to their impact on productivityand staff retention. Human resource management practices are essential to keeping a company'sworkforce and boosting its overall productivity. Studies of HR procedures are common these days.Human resource management approaches have become the primary obstacles for all businesses sincehuman workers are the major assets of both the industrial and service sectors. Successful humanresource management (HRM) initiatives pay off in a number of ways, including increased profits, publicfavor, and employee loyalty. The retention of key employees is an issue that affects every firm. Thisanalysis looks at how human resource management methods affect employee retention rates. Researchshows that retention rates may be improved by implementing HRM policies and practices. Methods ofhuman resource management can have a direct and significant impact on the rate at which employeesare retained. When employees have a favorable impression of their employer's human resourcemanagement methods, they are more likely to remain with the company for the long time. Humanresource management methods are now the key drivers of employee engagement, contentment, andloyalty. Keeping the best employees around can help to save money and boost the bottom line. Theauthors discovered that HRM procedures had a beneficial effect on staff retention. Human resourcemanagement (HRM) techniques that boost worker happiness and loyalty should be a top priority forfirms and their managers if they want to maintain their employees.